Accounting Transformation to Determine Fraud: The Role of Digital Accounting and Forensic Accounting with Internal Control - Daud, Maiercherinra; Patandean, Eben Haezer Basran (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The increasing complexity of financial transactions in the digital era has heightened the need for effective fraud detection mechanisms. Digital accounting and forensic accounting have emerged as key innovations, but their effectiveness in preventing fraud remains influenced by the internal systems within organizations. This study aims to examine the mediating role of internal control in the relationship between digital accounting, forensic accounting, and fraud detection effectiveness. To achieve this objective, the research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 110 financial professionals working in various organizations across Makassar, Indonesia. The findings reveal that digital accounting and forensic accounting do not have a direct significant effect on fraud detection. However, both significantly influence internal control, which in turn has a strong and positive impact on fraud detection. These results underscore the central role of internal control systems in enhancing the effectiveness of accounting technologies in fraud prevention. In conclusion, the study highlights the strategic importance of strengthening internal controls as an integrative platform for technological and investigative tools in combating financial fraud, and offers valuable insights for future research and organizational policy development.